An SRR based miniature implantable antenna with a slit loaded ground at MedRadio and ISM bands for biotelemetry applications - Yamac, Yunus E.; Basaran, Siddik C. (WILEY, 2020)
A miniaturized implantable microstrip split-ring antenna (IMSRA) is proposed for wireless biotelemetry. The IMSRA takes up a miniaturized volume of 153.35 mm(3)(10.5 x 11.5 x 1.27) and provides a dual-band operation in 360 to 620 MHz and 2.32 to 2.54 GHz that covers The Medical Device Radiocommunications Service (MedRadio) (401-406 MHz) and Industrial, Scientific, and Medical (ISM) (433-434 MHz and 2.4-2.48 GHz) bands. The principal part of the radiator consists of three homocentric split-ring elements. In addition, three conductor paths located between the split rings are used for precise adjustment of the frequency. In order to reduce the antenna size, a shorting pin is appropriately inserted between one of the metallic rings and the ground plane. The impedance matching of the antenna is improved by the use of a hook-shaped slit placed on the ground plane. For verification of the in vivo operation, the proposed IMSRA was measured in two separate skin-mimicking gels for MedRadio and ISM bands. A prototype was also tested in the skin tissue sample of a donor rat. The proposed antenna offers 53% (360 similar to 620 MHz) bandwidth at 490 MHz and 9% (2.32 similar to 2.54 GHz) bandwidth at 2.43 GHz. The IMSRA exhibits well-behaved radiation patterns and SAR values at the respective bands.
Keywords: biotelemetry; implantable antenna; MedRadio and ISM bands; split ring elements; MONOPOLE ANTENNA; DESIGN; COMPACT; SKIN; WLAN; MICS; Computer Science; Engineering